Computational performance of a generalized descent gradient method based algorithm with conformable fractional-order derivatives - de Andrade Bortoloti, Marcio Antônio (Journal of computational and applied mathematics, 2025)
In this paper, we perform an analysis of the Descent Gradient Method (DGM) within the context of the conformable fractional derivatives. We explore the mathematical properties of functions with continuous Lipschitz gradients. Notably, this fractional derivative approach significantly reduced computational effort when compared to the conventional DGM. Additionally, we present a detailed numerical example to prove the high performance of this generalized DGM algorithm.